OPTIMALISASI FACEBOOK ADS UNTUK MENINGKATKAN EFEKTIVITAS DIGITAL MARKETING PADA UMKM - Nurrohman, Rosyid; Sanistasya, Poppy Alvianolita; Herdianto, Bayu Putra; Tuzzahrah, Fatimah; Masluchah, Lisa Febrianti; Mahmudah, Zahra Aulia (Universitas Islam 45 Bekasi, 2025)
The main challenge in developing Micro, Small, and Medium Enterprises (MSMEs) in the digital era is low digital literacy and limited use of promotional platforms such as Facebook Ads. This community service activity aims to enhance MSME actors’ capacity to optimize Facebook Ads as an effective and affordable digital marketing tool. The implementation method involves practical training and interactive workshops engaging 10 MSME participants in Samarinda, with direct guidance from university students. Evaluation was conducted using pretest and posttest assessments. The results show that participants’ average understanding scores increased from 8.1 to 14, indicating a 73% improvement, which reflects significant enhancement in digital marketing hard skills. Moreover, participants successfully created business accounts, designed ad campaigns, and interpreted ad performance independently. The program also positively influenced participants’ self-confidence and readiness to promote their products digitally. These findings suggest that targeted digital marketing training can significantly empower MSME actors in the adoption of online promotional strategies, fostering more competitive and digitally savvy business practices.